The scapegoat theory of exchange rates: The first tests - Marcel Fratzscher; Lucio Sarno; Gabriele Zinna (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This paper provides an empirical test of the scapegoat theory of exchange rates (Bacchetta and van Wincoop 2004, 2011). This theory suggests that market participants may at times attach significantly more weight to individual economic fundamentals to rationalize the pricing of currencies, which are partly driven by unobservable shocks. Using novel survey data which directly measure foreign exchange scapegoats for 12 currencies and proprietary data on order flow, we find empirical evidence that strongly supports the scapegoat theory of exchange rates, with the resulting models explaining a large fraction of the variation and directional changes in exchange rates.
Keywords: F31; G10; 330; scapegoat; exchange rates; economic fundamentals; survey data